Front end customer relationship management (CRM) for UTM alumni - Naharu, Nasrah (2010)
Many strategies have been formulated to help a company in achieving it’s objectives. One of the most popular strategy that has been adopted among researchers and business sponsor nowadays is Customer Relationship Management (CRM). The purpose of using CRM in an organization is to improve marketing productivity, win the customer, provide good quality of service and offer good product to the customer. Realizing this , Higher education take the opportunities move from traditional turned to automation of internal business and organizational processes. From internal business process, higher education is moving to external business process to focus more on their customers. The customers of the higher education organizations are the students, alumni, donors, faculty members and staff members. The nature of relationships between alumni and organization can be considered as temporal. In fact, this study proposes that CRM approach will help alumni to reach their objectives. The application front end system is considered appropriate to be used as a problem solver of the Alumni Liaison Unit in higher education institution.